The role of subclinical psychopathic traits on experimentally induced self- and other-compassion - Lobbestael, Jill; Freund, Vanessa L.; Geschwind, Nicole; Meesters, Cor; Peeters, Frenk P. M. L. (Frontiers in Behavioral Neuroscience, 2022)
Psychopathic traits come with high levels of anger and aggression. Since previous studies showed that compassion can mitigate both anger and aggression, the current research puts compassion forward as a possible target to alleviate psychopathy’s destructive patterns. Specifically, the present study explored the influence of subclinical psychopathic traits – as well as its three subcomponents egocentricity, callousness, and antisociality – on the efficacy of experimentally induced self- and other-compassion. This paper is part of a larger study in which student and community participants (N=230, Mage=27.41, 65.2% female) completed a psychopathic trait questionnaire to assess their dimensional level of psychopathy, filled out state self- and other-compassion questionnaires, and were randomized to participate in an experimental self- or other-compassion induction. It was expected that psychopathic traits would positively relate to increases in self-compassion but negatively relate to increases in other-compassion. Baseline levels of both self- and other-compassion negatively related to psychopathy. Overall, as expected, the results on change scores show that subclinical psychopathic traits positively related to a stronger increase in self-compassion, irrespective of the type of compassion induction. This positive relation between a stronger increase in self-compassion and psychopathy total and callousness was more pronounced after the self-compassion induction, rather than after the other-compassion induction. Psychopathic traits did not differentially influence changes in other-compassion. One implication of this study is that high psychopathic and callousness traits predispose to profit extra from targeting self-compassion. Furthermore, psychopathic traits do not hinder increasing compassion for others. These findings suggest that compassion is a promising intervention to improve the well-being of people with elevated subclinical psychopathic traits and those around them. Although further research is needed to assess the impact of compassion on anger and aggression specifically, and on clinical psychopathy, the current study suggests that both self- and other-compassion may be useful intervention targets in case of elevated psychopathic traits.